Efficient Diastereoselective Three‐Component Synthesis of Pipecolic Amides. Issue 31 (29th May 2019) - van der Heijden, Gydo; van Schaik, Timo B.; Mouarrawis, Valentinos; de Wit, Martin J. M.; Velde, Christophe M. L. Vande; Ruijter, Eelco; Orru, Romano V. A.
Abstract : An efficient Ugi‐type three‐component reaction (U‐3CR) for the synthesis of pipecolic amides is reported. The U‐3CR between electronically diverse isocyanides, carboxylic acids and 4‐substituted Δ1‐piperideines proceeds in a highly diastereoselective fashion. The Δ1‐piperideines are obtained by NCS‐mediated oxidation of the corresponding 4‐substituted piperidines, which in turn are generated by an efficient two‐step procedure involving the alkylation of 4‐picoline and subsequent catalytic hydrogenation of the pyridine ring. We demonstrate the utility of this U‐3CR, in combination with the convertible isocyanide 2‐bromo‐6‐isocyanopyridine, in the synthesis of the anticoagulant argatroban. Abstract : An efficient Ugi‐type three‐component reaction (U‐3CR) for the diastereoselective synthesis of pipecolic amides is reported. The combination of this U‐3CR with the convertible isocyanide 2‐bromo‐6‐isocyanopyridine afforded the anticoagulant argatroban in a highly efficient manner.